The EU's future role on the global stage - Ruser, Alexander; Anheier, Helmut K. (Global policy, 2014)
What role will the EU play on the global stage? The struggle of some of its members in the current economic crisis, its apparent inability to punch its political weight in international negotiations (e.g. the climate summit in Warsaw in 2013) or play a dominant part in international crisis management (the Arab Spring, Syria) cast doubt on the capabilities of the EU as a global player. In order to regain its strength, the EU has to deal with pressing economic and political questions. It has to provide a credible and feasible road map for economic recovery and social cohesion. At the same time, it has to increase the effectiveness and efficiency of European governance without risking its legitimacy. To preserve its actor capacity, the EU must make sure that the (presently unequally distributed) growth potential stemming from research and development serves the economic recovery of the union as a whole. At the same time, successful efforts to make European governance more efficient must be accompanied by additional safeguard measure to ensure its legitimacy.